To determine which equation has a solution of \(-12 \frac{1}{2}\), we first convert \(-12 \frac{1}{2}\) to an improper fraction:
\[ -12 \frac{1}{2} = -12 - \frac{1}{2} = -\frac{24}{2} - \frac{1}{2} = -\frac{25}{2} \]
Now we will solve each equation to see which one has this solution.
-
Equation: \(x + 1 = 12\) \[ x = 12 - 1 = 11 \] Not \(-\frac{25}{2}\).
-
Equation: \(x + 1 = \frac{1}{2}\) \[ x = \frac{1}{2} - 1 = \frac{1}{2} - \frac{2}{2} = -\frac{1}{2} \] Not \(-\frac{25}{2}\).
-
Equation: \(x - 12 = 1\) \[ x = 1 + 12 = 13 \] Not \(-\frac{25}{2}\).
-
Equation: \(x - 1 = -12\) \[ x = -12 + 1 = -11 \] Not \(-\frac{25}{2}\).
-
Equation: \(x + 12 = -1\) \[ x = -1 - 12 = -13 \] Not \(-\frac{25}{2}\).
Based on the evaluations above, none of the given equations yield a solution of \(-12 \frac{1}{2}\) or \(-\frac{25}{2}\). Please double-check the problem statement or the equations, as none of them match the specified solution.